Adjusting Reported COVID-19 Deaths for the Prevailing Routine Death Surveillance in India - Shewade, Hemant Deepak; Parameswaran, Giridara Gopal; Mazumder, Archisman; Gupta, Mohak (Frontiers in Public Health, 2021)
In India, the ‘low mortality’ narrative based on reported COVID-19 deaths may be causing more harm than benefit. The extent to which COVID-19 deaths get reported depends on the coverage of routine death surveillance (death registration along with medical certification of cause of death (MCCD)) and the errors in MCCD. In India, the coverage of routine death surveillance is 18.1%. This is compounded by the fact that COVID-19 death reporting is focused among reported cases and the case detection ratio is low. To adjust for the coverage of routine death surveillance and errors in MCCD, we calculated a correction (multiplication) factor at national and state level to produce an estimated number of COVID-19 deaths. As on July 31, 2020, we calculated the infection fatality ratio (IFR) for India (0.58:100 – 1.16:100) using these estimated COVID-19 deaths; this is comparable with the IFR range in countries with near perfect routine death surveillance. We recommend the release of excess deaths data during COVID-19 (at least in states with high death registration) and post-mortem COVID-19 testing as a surveillance activity for a better understanding of under-reporting. In its absence, we should adjust reported COVID-19 deaths for coverage of routine death surveillance and errors in MCCD. This way we will have a clear idea of the true burden of deaths and our public health response will be never be inadequate. We recommend that ‘reported’ or ‘estimated’ is added before the COVID-19 death data and related indicators for better clarity and interpretation.